EFFECT OF SOME AGRICULTURAL OPERATIONS ON THE GROWTH AND YIELD OF CHICKPEA (Cicer aritenium L.) (Nativa, 2024)
ABSTRACT: The study was carried out in the years 2022/2023 and included a field experiment in two locations (Rashidia and Alqosh districts in Iraq); each study contained 12 treatments resulting from combinations between two planting and harvest dates and three seeding rates for chickpea seeds: plantings in autumn and spring, with harvests on 5/15 and 6/1/2023; the sowing rates were based on different densities and the distance between the sowing lines (20-15-10 cm) was changed to obtain (150, 100 and 75) plants m-2. A randomized block design was used in a factorial arrangement with three replications. The results of the individual factors for the autumn planting dates and harvest date on 05/15 indicated significant superiority of these two dates in all the characteristics studied; From the results of the sowing rates, the average superiority of 75 plants m-2 in the characteristics of the number of pods plant-1 and the seed index is noted. In contrast, seeding rates exceeded 75 and 100 plants m-2 in the seed pod-1 number trait, while seeding rates exceeded 150 plants m-2 in plant height, lowest pod height, seed yield and biological characteristics, for both experimental locations.Keywords: plant-climate interactions; harvest dates; planting date; seeding rates. Efeito de algumas operações agrícolas no crescimento e rendimento do grão-de-bico (Cicer aritenium L.)  RESUMO: O estudo foi realizado nos anos 2022/2023 e incluiu um experimento de campo em duas localidades (distritos de Rashidia e Alqosh no Iraque); cada estudo continha 12 tratamentos resultantes de combinações entre duas datas de plantio e colheita e três taxas de semeadura para sementes de grão de bico,: plantios no outono e primavera, com colheitas em 15/5 e 1/6/2023; as taxas de semeadura foram baseadas em diferentes densidades e a distância entre as linhas de semeadura (20-15-10 cm) foi alterada para obtenção de (150, 100 e 75) plantas plantas m-2. Utilizou-se delineamento em blocos casualizados, em arranjo fatorial, com três repetições. Os resultados dos fatores individuais para as datas de plantio de outono e data de colheita em 15/05, indicaram superioridade significativa dessas duas datas em todas as características estudadas; a partir dos resultados das taxas de semeadura, nota-se a superioridade média de 75 plantas m-2 nas características do número de vagens planta-1 e o índice de sementes. Em contrapartida, as taxas de semeadura ultrapassaram 75 e 100 plantas m-2 na característica do número de sementes vagem-1, enquanto a taxa de semeadura ultrapassou 150 plantas m-2 na altura da planta, altura da vagem mais baixa, rendimento de sementes e características biológicas, para ambos os locais experimentais.Palavras-chave: interações planta-clima; datas de colheita; datas de plantio; taxas de semeadura.